Microfluidic Chip for the Electrochemical Detection of MicroRNAs: Methylene Blue Increasing the Specificity of the Biosensor - Poujouly, Claire; Le Gall, Jérémy; Freisa, Martina; Kechkeche, Djamila; Bouville, David; Khemir, Jihed; Gonzalez-Losada, Pedro; Gamby, Jean (Frontiers in Chemistry, 2022)
MicroRNAs (miRNAs) are biomarkers involved in biological processes that are released by cells and found in biological fluids like blood. Since the detection of such nucleic acids can easily be applied in the field of early diagnosis, the development of nucleic acid-based biosensors has significantly increased in the past ten years. These biosensors require to be sensitive, specific and rapid in order to be effective. The electrochemical biosensor presented in this work enables a fast detection in 30 minutes and, as a result of its integration in microfluidics, it presents a limit of detection as low as 1 aM. Concerning the specificity of electrochemical biosensors, several studies have been found in the literature reporting 1 base-mismatch with the base-mismatch located in the middle of the strand. Herein, we report an electrochemical nucleic acid biosensor integrated in a microfluidic chip allowing for a 1 base-mismatch specificity independently from the location of the mismatch in the strand. This specificity was improved using a solution of methylene blue, making possible to discriminate a partial hybridization from a complete and complementary hybridization.